2014
DOI: 10.1016/j.diabres.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Illness beliefs predict self-care behaviours in patients with diabetic foot ulcers: A prospective study

Abstract: Patients' beliefs are important determinants of foot-care practices. They may, therefore, also be influential in determining ulcer outcomes. Interventions aimed at modifying illness beliefs may offer a means for promoting self-care and improving ulcer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 25 publications
(38 reference statements)
5
64
2
3
Order By: Relevance
“…This challenges the relevance of recent findings by Vedhara et al (36) regarding the importance of DFU-specific beliefs in predicting foot self-care in those with active foot ulcers. While the foot self-care behaviors included in their report (checking of feet, inspecting inside of shoes, washing feet, soaking feet and drying between toes) may well be helpful in DFU prevention, they have little benefit in those with active DFU, where adherence to off-loading rather than preventive foot care is central to the healing of foot ulcers.…”
Section: Discussioncontrasting
confidence: 63%
“…This challenges the relevance of recent findings by Vedhara et al (36) regarding the importance of DFU-specific beliefs in predicting foot self-care in those with active foot ulcers. While the foot self-care behaviors included in their report (checking of feet, inspecting inside of shoes, washing feet, soaking feet and drying between toes) may well be helpful in DFU prevention, they have little benefit in those with active DFU, where adherence to off-loading rather than preventive foot care is central to the healing of foot ulcers.…”
Section: Discussioncontrasting
confidence: 63%
“…It is clear that the uptake and effectiveness of PPC require more than simply providing information to women about the importance of managing their reproduction and pregnancy planning 30. While such information may increase the awareness of women about PPC, underlying beliefs, emotional concerns, and social factors also need to be considered to ensure that the women become actively engaged with and benefit from PPC.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies had similarly underscored the effectiveness of beliefs on self-care behaviors [36, 37]. In this respect, the results of the study by Munni et al on diabetic mothers showed that 44–58% of them believed that they had to avoid eating some types of fish due to their effects on increasing excessive fetal activity, congenital anomalies, and other diseases.…”
Section: Discussionmentioning
confidence: 99%